PENGARUH DISIPLIN KERJA, KOMPETENSI DAN BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA PEGAWAI PADA DINAS PERKEBUNAN SUMATERA UTARA - Tanjung, Hasrudy (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2016)
This study aims to determine whether there  is influence of labor discipline against the employee satisfaction,  Is  there  any  effect  of  competence  on  employee  satisfaction,  Is  there  any  influence  of organizational  culture  on  employee  satisfaction,  Is  there  any  influence  of  labor  discipline  of organizational culture and Is there any influence between labor discipline competence and organizational culture on job satisfaction of employees at the Plantation Office of North Sumatra Province.The  population  in  this  study  were  all  employees  remain  on  duty  Plantation  North  Sumatra Province  which  amounted  to  130  people.  Sample  study  determined  using  census  sampling  or  sampling techniques  that  saturated  the  entire  study  population  sampled.  Data  were  analyzed  using  path  analysis model, classic assumption test and parameter estimation and hypothesis testing.Work  discipline  against  the  employee  satisfaction  has  a  positive  and  significant  impact, competencies  on  job  satisfaction  of  employees  have  a  positive  and  significant  impact.  Organizational culture on employee satisfaction has a positive and significant impact thus organizational culture needs to be preserved and enhanced back. Labor discipline of organizational culture on the Plantation Office of North  Sumatra  province  has  positive  and  significant  impact.  Labor  discipline  and  competence  through organizational culture on job satisfaction of employees at the Plantation Office of North Sumatra province has  a  positive  and  significant  influence,  and  thus  the  discipline  of  work  and  competence  through organizational culture needs to be preserved.Keywords: Work Discipline, Competence, Organizational Culture and Employee Job Satisfaction